Analisis Kebijakan Pendidikan Inklusif di Sekolah Dasar: Tantangan dan Peluang di Era Digital di Jawa Tengah - Bantali, Ampun; Arjuna, Achmad; Munadia, Munadia; Sazulhaq, Amru (ARZUSIN, 2025)
The purpose of this study is to discuss the analysis of inclusive education policy in elementary schools: challenges and opportunities in the digital era in Central Java in depth so that later it can be described related to the education policies carried out. In discussing the inclusive education policy in elementary schools, this study uses a field research method or known as a qualitative method with a Review Literature Systematic (SLR) reinforcement. The focus of this research is on challenges and opportunities in the digital era. The main sources of research are interviews and observations, while the corroborating sources are from relevant articles, published between 2020 and 2025, drawn from databases such as Google Scholar Elicit, and ResearchGate. The results of the study found that inclusive education in Indonesia faces many challenges and opportunities. The digital age has made it easier to get an education, but there are issues like digital ethics and online safety that need to be addressed. Technology is not used due to limited infrastructure and lack of teacher instruction. For inclusive education and equal access for students with special needs, cooperation between all parties, including parents and the government, is essential. This study found that there are challenges and opportunities in inclusive education in Indonesia, including in Central Java. Although the digital age allows more people to learn, ethical and online safety issues still need to be addressed. Therefore, school principals, teachers, and parents in Central Java work together to ensure that all students, especially those with special needs, receive quality education, policymakers must create curricula and training programs that are in accordance with national education and the goals of the regions to advance and improve.